APLIKASI GEOLISTRIK KONFIGURASI WENNER DALAM MENDETEKSI PENCEMARAN AIR TANAH AKIBAT GAMBUT PADA DESA SUNGAI TERAP - Juventa; ira kusuma dewi; Nasri MZ; Ichy Lucya Resta (JOURNAL ONLINE OF PHYSICS, 2020)
Sungai Terap Village, Betara District, Tanjung Jabung Timur Regency is one of the areas in Jambi Province which is composed of peat soil. Peat land in this village is used by the community as agricultural and plantation land. As a result, the peat soil is degraded and damaged, causing groundwater pollution. The application of the resistivity geoelectric method can answer the question of groundwater pollution. In the current method that is injected into the earth and measures the potential difference on the surface. Geoelectric measurements were carried out in 4 lines with a length of 200 meters, electrode separation of 10 meters and n = 4. From the measurement results, it was found that groundwater was polluted due to peat soil because it had a very small resistivity value, namely 0.625-2.064 Ωm. This is because the chemical content contained in the peat soil will be carried away by rainwater that enters the surface. The effect of sea water intrusion can also pollute groundwater through drainage channels built on the peatlands.